(untitled) (International Association of Biologicals and Computational Digest, 2022)
Oct3/4 is found in germ cells is crucial to control pluripotency during normal development. There is mounting evidence for an association between Oct3/4 and carcinogenesis. Thus Oct3/4 immunohistochemistry has been found in studies to be a useful diagnostic technique for pluripotent germ-cell cancers, providing fresh insights into the cancer’s histological heterogeneity. The aim is to study role of Oct3/4 expression in HER2/neu positive breast cancer patients. Paraffin embedded breast tumour tissues from 50 HER2/neu positive female breast cancer patients were enrolled in the study. Oct3/4 expression was studied by immunohistochemistry method and correlated with clinical and pathological parameters as well as disease status. Oct3/4 positivity was seen in 16% of HER2/neu positive breast cancer patients. No significant correlation of Oct3/4 expression with age, menopausal status, tumour size, histopathology, grade and BR score was observed. A trend of higher incidence of Oct3/4 expression was noted with lymph node positive (30%) than lymph node negative patients (07%). A significant higher incidence of Oct3/4 expression was noted in patients with advanced stage of disease (32%) as compared to patients with early stage of disease (04%) and in patients with relapse (44%) than patients in remission (10%). A significant higher incidence Oct3/4 expression was observed with respect to disease free survival in univariate survival analysis. In multivariate survival analysis, for disease free survival metastasis entered at step 1 and grade entered at step 2. For overall survival, metastasis is entered at step 1 as significant factor. The Oct3/4 gene expression may be implicated in self-renewal and tumorigenesis via activating its downstream target genes. It might serve as an important biomarker for contemplating the carcinogenesis, progression, metastasis, or invasive potential and prognosis of breast carcinoma. A larger prospective follow-up studies are recommended to further explore Oct3/4 significance.